Dumping social nas relações de trabalho: uma avaliação política da Política Pública de Tratamento Adequado das Disputas de Interesse - SILVA, Rodrigo Barbalho Desterro e (2020)
This dissertation has as its object the study of Brazilian Labor Justice Policy of Appropriate Treatment of Disputes of Interest, and its scope converges in the accomplishment of a political evaluation of the Policy, instituted by the Resolution 174, of 2016, of the Superior Council of Labor Justice, which incorporated institutional arrangements delimited by the National Council of Justice in earlier years through Resolution 125, of 2010. Adopts as its assumption the Contemporary Capitalist State Theory and its determinations of nature and space, and the contradictory and complex involvement with social dumping in labor relations, as a prior phenomenon derived from the relentless practice of violation and denial of labor rights in order to achieve a potential advantage over competition. The question its analyzed from a Marxian perspective, through the use of historical-dialectical materialism and, therefore, we examine the historical designs that gives meaning to the Policy formulations as a state intervention. Thus, we start from a bibliographical and documental research, in order to allow the analysis of documents and data related do the Policy and its formulation process. Thus, it asks whether or not the policy has a propensity for naturalization and legitimation of social dumping through a state regulation practices, unfavorable to worker’s interests. It reflects about the process of institution of conciliation as a policy based on social-historical rescue that analyzes the idea of class conciliation as a culture with reflexes in the Labor Judiciary. It investigates the subject, their interests and rationalities and the way they express them in the Policy formulation process, trying to verify their influence degree on the Policy itself. It analyzes the institutional design and the components of the Policy and encourages the rethinking of politics in order to overcome the violence against the working class.